2013
DOI: 10.1038/ncomms3262
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ-induced PARylation promotes local DNA demethylation by production of 5-hydroxymethylcytosine

Abstract: Recent studies have shown that DNA demethylation goes through the conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) by Tet proteins. However, it is still unclear how the target regions for demethylation are distinguished within their genomic context. Here we show that the nuclear receptor peroxisome proliferator-activated receptor-g (PPARg) has the ability to direct local demethylation around its binding sites, the PPAR response elements (PPREs), during adipocyte differentiation. PPARg is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 37 publications
8
89
0
Order By: Relevance
“…Accordingly, both TET1 and 5hmC often localize to transcriptional start sites (16,17). With regard to nuclear receptors, it was reported previously that peroxisome proliferator-activated receptor-γ has the ability to direct local demethylation around its binding sites via recruitment of TET1 through peroxisome proliferator-activated receptor-γ-induced PARylation (18). In addition, TET3 up-regulation was shown to be responsible for glucocorticoid receptor-induced DNA hypomethylation in neural stem cells (19).…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, both TET1 and 5hmC often localize to transcriptional start sites (16,17). With regard to nuclear receptors, it was reported previously that peroxisome proliferator-activated receptor-γ has the ability to direct local demethylation around its binding sites via recruitment of TET1 through peroxisome proliferator-activated receptor-γ-induced PARylation (18). In addition, TET3 up-regulation was shown to be responsible for glucocorticoid receptor-induced DNA hypomethylation in neural stem cells (19).…”
Section: Discussionmentioning
confidence: 95%
“…[23][24][25][26] Thus, TFs with a TET-dependent demethylation function may comprise a functional subclass. However, because a limited number of TFs have been identified in this subclass, it is unclear how major this subclass is.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recently, several TFs, which play important roles in cellular differentiations, were reported to induce DNA demethylation by interacting with TET proteins. [23][24][25][26] However, it has not been elucidated whether RUNX1 also contributes to regulating DNA methylation. Here, we demonstrate that RUNX1 contributes site-directed DNA demethylation by recruitment of DNA demethylation enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…adiponectin and adiponectin receptor 2, that are targeted by PPARγ, showed differential methylation within their PPARγ DNA binding sites at later stages of adipogenesis (Takada et al, 2014). PPARγ has been shown to induce local DNA demethylation at its binding sites via poly(ADP-ribosyl)ation of the transcription factor/coactivator complex and subsequent recruitment of Tet proteins that oxidize 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine, resulting in the replacement of 5-mC by cytosine (Fujiki et al, 2013). It can be concluded that the DNA methylome of mature adipocytes develops early in the lineage differentiation, and that the large majority of adipocyte genes is 'ready' for transcriptional induction as early as the preadipocyte stage.…”
Section: Adipogenesismentioning
confidence: 99%